2021
DOI: 10.1093/ofid/ofab546
|View full text |Cite
|
Sign up to set email alerts
|

Bamlanivimab Efficacy in Older and High-BMI Outpatients With COVID-19 Selected for Treatment in a Lottery-Based Allocation Process

Abstract: Background Given the challenges associated with timely delivery of monoclonal antibody (mAb) therapy to outpatients with Covid-19 who are most likely to benefit, it is critical to understand the effectiveness of such therapy outside the context of clinical trials. Methods Case-control study of 1257 adult outpatients with Covid-19, ≥ 65 years of age or with BMI ≥ 35, who were entered into a lottery for mAb therapy. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 11 publications
(14 reference statements)
0
6
0
Order By: Relevance
“…The COVID variants of interest in the studies included 21C (Epsilon), 20E (EU1), and B.1.1.7 (Alpha). Seven additional studies were identified in January 2023, and these were included in our analysis ( Chilimuri et al, 2022 ; Cooper et al, 2021 ; Iqbal et al, 2021 ; Leavitt et al, 2021 ; Murillo et al, 2022 ; Rainwater-Lovett et al, 2021 ; Rubin et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…The COVID variants of interest in the studies included 21C (Epsilon), 20E (EU1), and B.1.1.7 (Alpha). Seven additional studies were identified in January 2023, and these were included in our analysis ( Chilimuri et al, 2022 ; Cooper et al, 2021 ; Iqbal et al, 2021 ; Leavitt et al, 2021 ; Murillo et al, 2022 ; Rainwater-Lovett et al, 2021 ; Rubin et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…21 It is noteworthy that other investigators have addressed this limitation by examining outcomes in patients for whom, due to supply limitations, a lottery-based approach to equitable patient allocation was applied. 22 However, some lotteries were more restrictive than the EUA qualifications, restricting to either high BMI ≥35 or age ≥65 patients. 22 Collectively, varied approaches and investigations corroborate the benefit of neutralizing monoclonal antibody therapy such as bamlanivimab for those periods of time when viral variants in circulation demonstrate susceptibility.…”
Section: Discussionmentioning
confidence: 99%
“…22 However, some lotteries were more restrictive than the EUA qualifications, restricting to either high BMI ≥35 or age ≥65 patients. 22 Collectively, varied approaches and investigations corroborate the benefit of neutralizing monoclonal antibody therapy such as bamlanivimab for those periods of time when viral variants in circulation demonstrate susceptibility.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Food and Drug Administration has issued Emergency Use Authorization (EUA) for multiple monoclonal antibodies (“mAbs”) for outpatients with COVID-19 and mild to moderate symptoms who are at high risk for severe disease [ 1–3 ] based on evidence that the early administration of mAbs significantly reduces the need for hospitalization [ 4–6 ]. Multiple studies have confirmed the effectiveness of mAbs in reducing rates of hospitalization under real-world conditions [ 7 , 8 ]. The current EUAs for bamlanivimab and etesevimab, casirivimab and imdevimab, and sotrovimab contain a list of qualifying risk factors for severe disease.…”
mentioning
confidence: 99%